Penyuluhan Pemanfaatan Kurma Pada Ibu Menyusui Di Desa Sokaraja Kulon - Margiana, Wulan; Muflihah, Ima Syamrotul (Jurnal Pengabdian Dharma Bakti, 2020)
The potential of dates in the health sector has long been known. The benefits of consumption of dates, also affect mothers who are breastfeeding. The nutritional needs of infants up to the age of six months are obtained through breast milk. Sufficient milk production, both in quantity and quality, will determine the growth of the baby. Efforts to achieve optimal infant nutrition up to the age of six months can only be done through improving maternal nutrition. This illustrates that the food consumed by nursing mothers is very influential on the production of breast milk. Based on observations of breastfeeding mothers in the Sokaraja Kulon Village there are still many who do not know the benefits of dates on nursing mothers. The goal is to increase knowledge about the benefits of dates for nursing mothers, and increase milk production. The method of implementing community service is the provision of health education about the benefits of dates on breastfeeding with the method of learning by doing. The result is increased knowledge in mothers and increased milk production.Â Keywords: Dates, the benefits of dates